THE ROLE AND SCOPE OF TRANSLATION STUDIES IN THE PRESENT - Sheraliyeva, Shaxnoza (Журнал иностранных языков и лингвистики, 2023)
In this article, we want to examine the role and scope of translation in a globalized world. How translators play an important role in building a bridge between two different cultures, languages ​​, and traditions. This article gives an overview of the many perspectives from which translation becomes an important part for us and of interdisciplinary research. How bright and beautiful is the future of translation? Translation studies, translation theory, and translation courses are introduced and implemented worldwide at the university level.